On properties of Bernstein-typ operator p0lynomials approximating the Urison operator. - Demkiv, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We generalize properties of the Bernstein polynomials to the Bernstein-type operator polynomialsapproximating the Urison operator.